Resistance training and reduction of treatment side effects in prostate cancer patients - Galvao, D.; Nosaka, K.; Taaffe, D.; Spry, N.; Kristjanson, Linda; McGuigan, M.; Suzuki, K.; Yamaya, K.; Newton, R. (Lippincott Williams & Wilkins, 2006)
Purpose: To examine the effect of progressive resistance training on muscle function, functional performance, balance, body composition, and muscle thickness in men receiving androgen deprivation for prostate cancer. Methods: Ten men aged 59-82 yr on androgen deprivation for localized prostate cancer undertook progressive resistance training for 20 wk at 6 to 12 repetition maximum (RM) for 12 upper and lower-body exercises in a university exercise rehabilitation clinic. Outcome measures included muscle strength and muscle endurance for the upper and lower body, functional performance (repeated chair rise, usual and fast 6m walk, 6m backwards walk, stair climb, and 400m walk time), and balance by sensory organization test. Body composition was measured by dual-energy x-ray absorptiometry and muscle thickness at four anatomical sites by B-mode ultrasound. Blood samples were assessed for prostate specific antigen (PSA), testosterone, growth hormone (GH), cortisol, and hemoglobin. Results: Muscle strength (chest press, 40.5%; seated row, 41.9%; leg press, 96.3%; P G 0.001) and muscle endurance (chest press, 114.9%; leg press, 167.1%; P G 0.001) increased significantly after training. Significant improvement (P G 0.05) occurred in the 6m usual walk (14.1%), 6m backwards walk (22.3%), chair rise (26.8%), stair climbing (10.4%), 400m walk (7.4%), and balance (7.8%). Muscle thickness increased (P G 0.05) by 15.7% at the quadriceps site. Whole-body lean mass was preserved with no change in fat mass. There were no significant changes in PSA, testosterone, GH, cortisol, or hemoglobin. Conclusions: Progressive resistance exercise has beneficial effects on muscle strength, functional performance and balance in older men receiving androgen deprivation for prostate cancer and should be considered to preserve body composition and reduce treatment side effects.